\[(a+b+c)^{2}=1\]
\[a^{2}+b^{2}+c^{2}+2ab+2bc+2ca=1\]
\[a^{2}+b^{2}+c^{2}-ab-bc-ca+3ab+3bc+3ca=1\]
\[\frac {1}{2}[(a-b)^{2}+(b-c)^{2}+(c-a)^{2}]+3(ab+bc+ca)=1\]
\[3(ab+bc+ca)\] will be maximum when \[\frac {1}{2}[(a-b)^{2}+(b-c)^{2}+(c-a)^{2}]=0\] i.e. is minimum =0.
Therefore max. \[ab+bc+ca=\frac {1}{3}\]

square a+b+c to get a^2 + b^2 + c^2 + 2(ab+bc+ca) = 1. Note that a^2 + b^2 + c^2 >= ab + bc + ca by AM-GM. thus ab + bc + ca <= 1/3 with equality iff a = b =c = 1/3

## Comments

Sort by:

TopNewest\[(a+b+c)^{2}=1\] \[a^{2}+b^{2}+c^{2}+2ab+2bc+2ca=1\] \[a^{2}+b^{2}+c^{2}-ab-bc-ca+3ab+3bc+3ca=1\] \[\frac {1}{2}[(a-b)^{2}+(b-c)^{2}+(c-a)^{2}]+3(ab+bc+ca)=1\] \[3(ab+bc+ca)\] will be maximum when \[\frac {1}{2}[(a-b)^{2}+(b-c)^{2}+(c-a)^{2}]=0\] i.e. is minimum =0. Therefore max. \[ab+bc+ca=\frac {1}{3}\]

Log in to reply

Nice proof!

Log in to reply

AM-GM kills it

Log in to reply

square a+b+c to get a^2 + b^2 + c^2 + 2(ab+bc+ca) = 1. Note that a^2 + b^2 + c^2 >= ab + bc + ca by AM-GM. thus ab + bc + ca <= 1/3 with equality iff a = b =c = 1/3

Log in to reply

The result also follows from the Rearrangement-Inequality

Log in to reply

solution?

Log in to reply

You can also use LaGrange Multipliers to solve for the maximum value right?

Log in to reply

1/3

Log in to reply

1/3 is the maximum

Log in to reply

0.33

Log in to reply

0.333333... To be precise (or simply 1/3, you meant 33/100)

Log in to reply

The max. value of ab + bc + ca is 0.

Log in to reply

that's wrong

Log in to reply

maximum is never 0

Log in to reply

Not always true

Log in to reply

Log in to reply

Log in to reply